Reinvention of Ojude-Oba Festival for Tourism and its Impact on the Host Community - Kukoyi, Ibrahim A.; Aremu, David A.; Ololajulo, Babajide O.; Balogun, Khidir B. (Àgídìgbo: ABUAD Journal of the Humanities, 2018)
This study examines the Ojude-Oba festival in Ogun State, by investigating the activities that characterized the festival from inception to present time, the changes that has occurred and the effect of the changes on the festival and the host community. Purposive sampling method was used to select 4 local policy makers and 2 festival planning committee members and key informant interviews were conducted with them. Systematic sampling method was used to select 400 respondents from the host community and close-ended questionnaire was used to gather data from them. Data were analyzed with the use of content analysis, simple percentages and chi-square. Findings from the study revealed that, Ojude-Oba festival was not touristic in nature at inception but has metamorphosed to a major tourism driver in Ogun State. Revival and incorporation of traditional Ijebu Age-Grade groups (Regbe-Regbe) parade, division of festival activities into Regbe-Regbe and Eleshin (Horse-Riders) contest with monetary reward attached, introduction of dues to participating groups and involvement of corporate bodies for sponsorship and branding were innovation in the Ojude-Oba festival. Majority (60.1%) of the changes discovered were deliberate and have resulted to increased participants’ population and also generate income for the host community. Reinventions in the festival have significant (p = 0.310) impact on the host community. The study concludes that the Ojude-Oba Festival has went through series of modification and reinvention of the festival activities. However, the changes experienced in the festival overtime has positive influence on the cultural practice. Hence, reinvention of the Ojude-Oba festival has transformed it to an event tourism product that is adding value to its host community.